Caracterização de laser aleatório em fibras poliméricas produzidas pela técnica de eletrofiação - Sousa Junior, Francisco Weldem Silva de (2019)
The great interest in random laser is due to the non-use of a reflective resonant cavity in order to obtain optical feedback, which is obtained using light scattering, which is a phenomenon present in everyday life and usually unwanted in optical experiments. In this work, random laser characterization results are presented in Eudragit L-100 fibers infiltrated with Rhodamine B and titanium dioxide (TiO2), using two concentrations of Rhodamine B, 10−2 and 10−3 M, besides the presence of different amounts of nanoparticles (0, 10 and 50 mg). The polymeric fibers have flexibility, synthesis have high productivity and low cost, being able to control factors like the scatter density and stiffness. In these samples, Rhodamine B was responsible for light amplification and TiO2 was used as a scatter center, as well as the fiber itself that acted as a scatter. In this system, the optical feedback was obtained by the scattering centers located randomly inside of the fiber, and the low probability of the light inserted in the medium is returned to its initial position, causing an incoherent feedback, which can be detected in the emission spectra, where spikes are not observed. The technique used for characterization of random laser emission was the laser induced luminescence technique in which we irradiated six samples with two different transverse rays of the incident beam. All samples presented laser type emission, with laser action threshold dependent on the area of the incident beam and with the position of the emission peak depending on the synthesis and excitation parameters. Finally, these materials were promising and demonstrated the possibility of laser emission tuning over a relatively wide range of the spectrum.